Structural Models, Classification of the Pharmacokinetics of Drugs, Substances - Bozorov Erkin Hodjievich; Kubaev Asaliddin Esirgapovich; Hodjiev Shohjakhan Erkin o’g’li (Scholars Digest Publishing, 2023)
This article shows the analytical results of the positive results obtained when using the "Discussion-Discussion" method of interactive teaching methods in explaining the topic to students.
Keywords: Mathematical modeling, structural models, structural elements, spatial structures, pharmacokinetic model, substance concentration, pharmacological processes.